SELECTION OF LABORATORY ASSISTANTS USING THE WEIGHTED PRODUCT METHOD TO SUPPORT DECISION MAKING - Rima Tamara Aldisa (Adisam Publisher, 2024)
This research aims to develop a decision support system (DSS) for selecting laboratory assistants using the Weighted Product (WP) method to support more effective decision making. The WP method was chosen because it is able to handle a number of different criteria and weights in the selection process. This study will identify the relevant criteria for the selection of laboratory assistants and assign weights to each criterion based on its importance. Next, the system will implement the WP method to calculate the total score for each assistant candidate based on the predetermined criteria and weights. The research results showed that K-6 with a score of 0.1284 got the highest ranking results and was followed by second place, namely K-8 with a score of 0.1269 and in third place with K-1 with a score of 0.1251. It is hoped that research can help and contribute to increasing efficiency and accuracy in decision making regarding the selection of laboratory assistants.